Análise da suscetibilidade do meio físico a movimentos gravitacionais de massa por meio de sistematização de zoneamento geoambiental - Moura, Cristiane Alessandra de [UNESP] (2014)
This thesis aimed to contribute with a methodological systematization to characterize and map areas of landslide susceptibility through the integration of the following methods: geoenvironmental mapping, photo interpretation, morphometric analysis of relief, morfostructure analysis and fracture map. This integration led to the classification of the landslide susceptibility of the physical environment. The morfostructural analysis allowed for the identification of sites with very specific environmental behavior (water infiltration or accumulation) of interest to this research. The fracture mapping identified areas with larger tectonic deformation in which intense infiltration and circulation of water occurs and, therefore, is ideal for an intense weathering of rocks. The synthesis product obtained through this integration was the Landslide Susceptibility Map of the physical environment, which was efficient in the detection of these phenomena, since it led to the identification of areas with greater tendencies to be affected by them